IMPLEMENTASI MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS III SDN 015 TANDUN KECAMATAN TANDUN KABUPATEN ROKAN HULU - Subrina Subrina; Neni Hermita; Guslinda Guslinda (Universitas Muhammadiyah Purwokerto, 2019)
Civics learning at school is an easy and fun lesson when a teacher is able to aplly a model that attracts students to learn. But in reality so far there are still many teachers who use conventional learning models so that learning becomes boring and students do not participate in the learning process which results in low student learning outcomes. This study aims to determine the differences in PKn learning outcomes before and after implementing the Quantum Teaching model. The type of research used in this study is quantitative research with experimental methods. The form of this study was pre-experimental (non-design) ukwith one-group pretest-posttest design. This research was conducted in class III of SDN 015 Tandun, Tandun District, Rokan Hulu Regency, which amounted to 20 students. Based on the results of the study obtained an average pretest that is equal to 39.75. while the posttest average is 70.25. The average N-Gain value is 0.52 with moderate interpretation. The results of the t test are obtained that the tcount score is greater than t table or 58.08> 2.0930. This is in accordance with the Reject H0 criteria, if thitung> t table. This proves that there are significant differences in PKn learning outcomes of grade 3 students of SDN 015 Tandun between before implementing the quantum teaching model and after implementing the quantum teaching model.